Prolactin Promotes Breast Cancer Cell Migration through Actin Cytoskeleton Remodeling - da Silva, Priscilla Ludovico; do Amaral, Vinicius Cestari; Gabrielli, Valentina; Montt Guevara, Maria Magdalena; Mannella, Paolo; Baracat, Edmund Chada; Soares-Jr, Jose Maria; Simoncini, Tommaso (Frontiers in Endocrinology, 2015)
The role of prolactin on breast cancer development and progression is debated. Breast cancer progression largely depends on cell movement and on the ability to remodel the actin cytoskeleton. In this process, actin-binding proteins are requested to achieve fibrillar actin de-polymerization and relocation at the cell membrane. Kinases such as focal adhesion kinase (FAK) are later required to form actin/vinculin-enriched structures called focal adhesion complexes, which mediate firm adhesion to the extracellular matrix. These controllers are regulated by c-Src, which forms multiprotein signaling complexes with membrane receptors and is regulated by a number of hormones, including prolactin. We here show that breast cancer cells exposed to prolactin display an elevated c-Src expression and phosphorylation. In parallel, increased moesin and FAK expression and phosphorylation are found. These molecular changes are associated to relocation to the plasma membrane of cytoskeletal actin fibers and to increased horizontal cell movement. In conclusion, prolactin regulates actin remodeling and enhances breast cancer cell movement. This finding broadens the understanding of prolactin actions on breast cancer cells, highlighting new pathways that may be relevant to on breast cancer progression.